Pemanfaatan Aplikasi Photomath Pada Pembelajaran Matematika: Systematic Literature Review - Nur Elisah Nasution; Yahfizham Yahfizham (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
This research aims to analyze meta data related to the use of the Photomath application. This research uses the Systematic Literature Review (SLR) method. This systematic review identified 11 studies via the Google Scholar database published in 2020-2023. Data collection was carried out by collecting all articles related to the use of the photomath application, with selection criteria and using the PRISMA procedure as a research instrument guide. The research results show that the Photomath application provides a positive, effective and practical learning experience in solving mathematics problems. Training in the use of mathematics applications is considered important to help students understand mathematics learning material.